Adaptation and Validation of the Polish Version of the 10-Item Mobile Phone Problematic Use Scale - Mach, Anna; Demkow-Jania, Marta; Klimkiewicz, Anna; Jakubczyk, Andrzej; Abramowska, Małgorzata; Kuciak, Anna; Serafin, Piotr; Szczypiński, Jan; Wojnar, Marcin (Frontiers in Psychiatry, 2020)
Pathological use of smartphones may be the biggest non-drug addiction of the 21st century. Therefore, rapid screening tools designed for easy identification of people with problematic mobile phone use are needed. The main aim of the present study was to validate a short version of the Mobile Phone Problematic Use Scale (MPPUS-10) in the Polish population. The study comprised 640 university students aged 18–38 years. We used a self-report questionnaire that included questions regarding socio-demographic variables and Polish versions of the Mobile Phone Problem Use Scale (MPPUS-10), Mobile Phone Addiction Assessment Questionnaire (MPAAQ in Polish KBUTK), and Internet Addiction Test (IAT) by Kimberly Young. The analysis showed high reliability for the final Polish version of MPPUS-10 (Cronbach’s α = 0.78) and confirmed a significant correlation between the MPPUS-10 and the MPAAQ, which was previously used in Poland (rho = 0.56; p < 0.001). Due to the poor correlation of item number 10 with other items, we suggest dropping this item and using the nine-item Polish version. Our result also confirmed significant correlation between the MPPUS-10 and the IAT (rho = 0.54; p < 0.001). The contribution of the study is the Polish validation and adaptation of the MPPUS-10 scale with confirmed psychometric values. It provides a quick and convenient screening tool to assess problematic mobile phone use. Our results also indicate the need for a revision of available diagnostic tools in Poland.